The role and importance of accounting information system in the context of digitalization - Haje, P; Arystanbaeva, A; Оralbaeva Zh; Kupenova, Zh (Farabi Journal of Social Sciences, 2019)
Information is an essential life resource that is practically understood as necessary and useful data presented in a convenient way, in accordance with the requirements of the user. An information system can be defined as a combination of information resources, processes, and people who collect, transform, and distribute information to organizations. There are many different types of information systems. The accounting system is understood as a certain integrity or set of accounting elements that are in relationship with each other. This system includes a logical complex, which refers information aimed at the correct measurement of the final results of activities in order to ensure the interests of the economic entity and the state. The optimal accounting system will be one that meets the requirements of accuracy, timeliness, low cost and eliminates the possibility of theft or fraud, etc. To date, primary accounting remains insufficiently orderly, time-consuming and poorly organized, and this hinders the development of integrated information processing systems. The main objective of primary accounting is not only to collect, measure and process information, but also to provide feedback in the preparation and decision-making. Increasing the level of automation and widespread use of various types of computer technology at all stages of the accounting process makes it possible to abandon the primary documents in the form of paper. Key word: Information, primary accounting, accounting system, automation.